Family Structure and Child Labor in Indonesia: Evidence from Widowed and Divorced Single-Mother Households - Bayu Kharisma (Economics Development Analysis Journal, 2026)
This study examines whether child labor differs between households headed by divorced mothers and those headed by widowed mothers in Indonesia. Using IFLS wave 5 data, the analysis estimates associations using an instrumental variables approach. The estimates indicate a higher likelihood of child labor among children living with divorced single mothers than among children living with widowed single mothers. The difference is larger for girls in divorced mother households relative to girls in widowed mother households. These findings support stronger enforcement of child support after divorce to reduce financial pressure on single mothers. Targeted social and psychosocial support may be especially relevant for girls in divorced mother households. Skills training and employment support for divorced single mothers may also reduce the need for children to contribute labor during schooling years